Study of effect of intra-umbilical oxytocin along with active management in third stage of labor - Verma, Neetu; Soni, Monica; Singh, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of the study was to determine effect of intra-umbilical oxytocin along with active management on duration and amount of blood loss in 3rd of stage of labor. Methods: This was a hospital based prospective, randomized, case-control study conducted in the department of OBG between 1st September 2019 to 31st December 2020. After obtaining permission from ethical committee, screening of inclusion and exclusion criteria and informed consent of participants, 300 cases were enrolled. In group A (control) 20 ml normal saline and in group B (case) 20 IU oxytocin diluted in normal saline to make a 20 ml solution was given intra-umbilically along with standard active management of third stage labor. The data was systematically recorded and analysed. Results: Both the groups were comparable in terms of demographic data. A statistically significant reduction in the duration of third stage of labor (1.83±0.64 min in group B vs 2.92±0.79 min in group A), amount of blood loss (203.73±62.11 ml in group B vs 328.83±87.18 ml group A) and fall in haemoglobin (9.28±1.03 g/dl in the study group A vs 9.97±1.28 g/dl in group B) and haematocrit (31.20±3.05% in study group A vs 33.60±3.31% in study group B) were noted, taking p value significant <0.05. Conclusions: Intra-umbilical oxytocin was associated with a significant reduction in duration and amount blood loss in third stage of labor.